Russia and the West. Issue 4 (21st April 2018) - Unknown
Abstract : Russia and the West are engaged in an ongoing strategic confrontation that shows few signs of relenting. While it is to an extent moderated by the practical need for cooperation on important security issues, Cold War-era logic is likely to prevail in the medium term. The key challenge is to develop clear rules for managing the confrontation.